Common Dermatoses in Children Referred to a Specialized Pediatric Dermatology Service in Mexico: A Comparative Study between Two Decades. (14th October 2012) - Del Pozzo-Magaña, Blanca Rosa; Lazo-Langner, Alejandro; Gutiérrez-Castrellón, Pedro; Ruiz-Maldonado, Ramón
Abstract : Background . Skin diseases among pediatric patients differ from those in adults. Epidemiological studies are scarce, and those performed in Mexican population date back thirty years. It is likely that these diseases might have changed their frequency. Material and Methods . Retrospective study in first-time patients referred to a pediatric dermatology service between January 1994 and December 2003. Demographics and diagnosis were recorded and compared with the results of a previous study performed in the same institution. Results . We included 5250 patients (52.55% female, 47.47% male) with 6029 diagnoses. The most frequent dermatoses found were atopic dermatitis (14.59%), viral warts (6.62%), acne (5.53%), pityriasis alba (3.98%), melanocytic nevi (3.85%), xerosis (3.57%), keratosis pilaris (3.19%), seborrheic dermatitis (2.37%), hemangioma (2.26%), and papular urticaria (2.24%). Most dermatoses increased their frequency when compared to the previous study. Conclusion . The frequency of pediatric dermatoses in our institution has changed in the last two decades. Environmental and sociocultural factors and institutional policies might account for these results.